Oxidative capacity varies along the length of healthy human tibialis anterior. (25th March 2018) - Boss, Andreas; Heskamp, Linda; Breukels, Vincent; Bains, Lauren J; van Uden, Mark J.; Heerschap, Arend
Abstract : Key points: During exercise skeletal muscles use the energy buffer phosphocreatine. The post‐exercise recovery of phosphocreatine is a measure of the oxidative capacity of muscles and is traditionally assessed by 31 P magnetic resonance spectroscopy of a large tissue region, assuming homogeneous energy metabolism. To test this assumption, we collected spatially resolved spectra along the length of human tibialis anterior using a home‐built array of 31 P detection coils, and observed a striking gradient in the recovery rate of phosphocreatine, decreasing along the proximo‐distal axis of the muscle. A similar gradient along this muscle was observed in signal changes recorded by 1 H muscle functional MRI. These findings identify intra‐muscular variation in the physiology of muscles in action and highlight the importance of localized sampling for any methodology investigating oxidative metabolism of this, and potentially other muscles. Abstract: The rate of phosphocreatine (PCr) recovery ( k PCr ) after exercise, characterizing muscle oxidative capacity, is traditionally assessed with unlocalized 31 P magnetic resonance spectroscopy (MRS) using a single surface coil. However, because of intramuscular variation in fibre type and oxygen supply, k PCr may be non‐uniform within muscles. We tested this along the length of the tibialis anterior (TA) muscle in 10 male volunteers. For this purpose, we employed a 3T MR system with a 31 P/ 1 H volume transmit coil combined with a home‐built 31 P phased‐array receive probe, consisting of five coil elements covering the TA muscle length. Mono‐exponential k PCr was determined for all coil elements after 40 s of submaximal isometric dorsiflexion (SUBMAX) and incremental exercise to exhaustion (EXH). In addition, muscle functional MRI ( 1 H mfMRI) was performed using the volume coil after another 40 s of SUBMAX. A strong gradient in k PCr was observed along the TA ( P  < 0.001), being two times higher proximally vs . distally during SUBMAX and EXH. Statistical analysis showed that this gradient cannot be explained by pH variations. A similar gradient was seen in the slope of the initial post‐exercise 1 H mfMRI signal change, which was higher proximally than distally in both the TA and the extensor digitorum longus ( P  < 0.001) and strongly correlated with k PCr . The pronounced differences along the TA in functional oxidative capacity identify regional variation in the physiological demand of this muscle during everyday activities and have implications for the bio‐energetic assessment of interventions to modify its performance and of neuromuscular disorders involving the TA. Key points: During exercise skeletal muscles use the energy buffer phosphocreatine. The post‐exercise recovery of phosphocreatine is a measure of the oxidative capacity of muscles and is traditionally assessed by 31 P magnetic resonance spectroscopy of a large tissue region, assuming homogeneous energy metabolism. To test this assumption, we collected spatially resolved spectra along the length of human tibialis anterior using a home‐built array of 31 P detection coils, and observed a striking gradient in the recovery rate of phosphocreatine, decreasing along the proximo‐distal axis of the muscle. A similar gradient along this muscle was observed in signal changes recorded by 1 H muscle functional MRI. These findings identify intra‐muscular variation in the physiology of muscles in action and highlight the importance of localized sampling for any methodology investigating oxidative metabolism of this, and potentially other muscles.